Telephone reminders to reduce non-attendance rate for endoscopy - Lee, C S (The Royal Society of Medicine, 2003)
Non-attendance at clinics and endoscopy units wastes resources and lengthens waiting lists. In a previous study elsewhere, a substantial proportion of patients claimed to have forgotten their appointment. We therefore assessed the value of telephoning patients a week before their booked day-case endoscopy. An observation period of two months was followed by an intervention period of two months in which patients were contacted by phone and asked if they wished to come for their investigation. A maximum of three separate attempts were made to contact each patient. Patients cancelling the appointment were replaced by others on the reserve list. The non-attendance rate was expressed as the percentage of unused beds. During the observation period 56 patients were admitted and 18 beds were unused. During the intervention period it was possible to contact 73 of 88 patients and 8 of these cancelled. 87 beds were available and 83 patients were admitted. When clerical error, overbooking and failure to replace patients were taken into account, the non-attendance rate declined from 23.3% during the observation period to 5.7% during the intervention period (P<0.05). The intervention seemed more effective in reducing non-attendance in outpatients referrals (0/48) than in general practitioner referrals (5/40).